2022
DOI: 10.3390/cells11081292
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the TRP-Oxidative Stress Axis in Metabolic Syndrome: Insights for Novel Therapeutic Approaches

Abstract: Metabolic syndrome (MS) is a complex pathology characterized by visceral adiposity, insulin resistance, arterial hypertension, and dyslipidaemia. It has become a global epidemic associated with increased consumption of high-calorie, low-fibre food and sedentary habits. Some of its underlying mechanisms have been identified, with hypoadiponectinemia, inflammation and oxidative stress as important factors for MS establishment and progression. Alterations in adipokine levels may favour glucotoxicity and lipotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 336 publications
(523 reference statements)
0
7
0
Order By: Relevance
“…Inflammation is an important event that contributes to metabolic imbalances; thus, tumour necrosis factor α (TNFα) and vascular endothelial growth factor (VEGF) levels (inflammatory mediators involved in obesity and glycaemia control (for review see: [ 33 , 40 ])) were evaluated in adipose tissue, liver, and pancreas samples obtained from animals fed either a standard or HS diet. HS diet-fed mice led to a greater release of these inflammatory mediators in adipose tissue and liver samples in comparison with those receiving standard diet, an effect which was further enhanced by ML204 injection ( Figure 4 A–D; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation is an important event that contributes to metabolic imbalances; thus, tumour necrosis factor α (TNFα) and vascular endothelial growth factor (VEGF) levels (inflammatory mediators involved in obesity and glycaemia control (for review see: [ 33 , 40 ])) were evaluated in adipose tissue, liver, and pancreas samples obtained from animals fed either a standard or HS diet. HS diet-fed mice led to a greater release of these inflammatory mediators in adipose tissue and liver samples in comparison with those receiving standard diet, an effect which was further enhanced by ML204 injection ( Figure 4 A–D; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Also in agreement, HS significantly increased BMI, hyperglycaemia, mesenteric fat deposition, glucose tolerance, hypercholesterolemia, and NAS score in comparison with mice receiving a standard diet. In addition, HS-fed mice presented with adipose tissue and liver inflammation characterised by increased levels of TNFα, a cytokine involved in adipocyte hypertrophy, fat deposition, insulin resistance, and hyperglycaemia (for review see: [ 33 ]). Higher VEGF levels were also noted in both liver and adipose tissue samples from HS mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, increased ROS can decrease adiponectin, further inflammation, endothelial dysfunction, and insulin resistance. Further progression of this condition will cause hypertension, dyslipidemia, diabetes type 2, atherosclerosis, and even cancer ( Araújo et al, 2022 ). Results from this study showed that KBPF intake could suppress ROS levels (ABTS, SOD data) as well as decrease major inflammatory cytokines (TNF-α, IL-6) significantly, potentially preventing the emergence and progression of metabolic disorders in its consumers ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Araújo et al examined the literature about the role of the TRP-oxidative stress axis in the pathogenesis and progression of metabolic syndrome, focusing on TRPV1, TRPA1 and TRPC5 in regulating the function of metabolic tissues and cells, and their connections with the central nervous system. They also discussed the potential of such TRP channels as therapeutical targets for metabolic syndrome [8].…”
Section: Metabolic Syndromementioning
confidence: 99%